Towards efficient water management in large-scale shale gas fields of China - Ke-Fan Cao; Yi Zeng; Xue-Shi Jin; Zhuo Chen; Yin-Hu Wu; Hong-Ying Hu (Journal of Water Reuse and Desalination, 2022)
China's shale gas industry is developing rapidly, but the associated challenges of water resources shortage and water pollution are becoming more and more prominent. Hydraulic fracturing, the core process of shale gas extraction, consumes a large amount of water and produces refractory wastewater, closely linking shale gas fields with water resources. In this context, this article is to (1) summarize the characteristics of water consumption and wastewater production in typical shale gas fields; (2) introduce the current status of water intake and internal reuse and treatment of shale gas wastewater (SGW); and (3) analyse the challenges of water management in shale gas field. In order to promote the sustainable development of the shale gas industry, it is necessary to establish an efficient water management system according to local conditions. Making use of municipal reclaimed water in fracturing, promoting external reuse of SGW, strengthening the monitoring and safety guarantee of water use, and formulating national or regional water management guidelines can improve the utilization efficiency of water resources in shale gas fields. HIGHLIGHTS The exploitation of shale gas has close connections with water-related issues.; Shale gas fields consume large quantities of water in the early stage.; Shale gas fields produce refractory wastewater in the later stage.; Shale gas fields need efficient water management systems.;